The global economic slowdown: Implications for the rural poor - Laborde Debucquet, David; Martin, Will (International Food Policy Research Institute, 2016)
Many developing countries seem likely to see a substantial downturn in economic growth over the 2015–2030 implementation period of the SDGs, compared with the recent years of strong growth. Since the 2015 WEO, the macroeconomic outlook has deteriorated further, with projected global growth for 2017 falling from 3.8 to 3.5 percent. However, a key result of this study is that projected declines in global poverty rates are not greatly affected by the anticipated slowdown in economic growth. Under the updated projections for 2030, the extreme poverty rate will be 5.2 percent compared to 4.8 percent. For most groups of countries and subgroups of populations, projected 2030 poverty rates will be within one percentage point of the levels projected under the optimistic outlook on global growth. However, there is some variation across countries, and even countries not directly affected by the recent global slowdown are likely to see long-term impacts. And despite this optimistic finding, we should be concerned that the movement in poverty rates is away from the SDG goal of complete elimination of poverty.